MEMBANGUN MOTIVASI GUNA MENINGKATKAN MINAT BACA MAHASISWA POLITEKNIK NEGERI MALANG - Sucipto, Hari; Wiwaha, Sigit Setya; Hakim, Muhammad Fahmi (DINAMIKA DOTCOM, 2018)
The purposes of this study are to analyze: (1) the effect of study habits to reading motivation of students, (2) the effect of the availability oftextbooks on reading motivation of students, (3) the influence of campusenvironment against reading motivation of students, (4)the effect of learning methods to motivate students to read, (5) the effects of habit of learning on student interest in reading, (6) the effect of the availability of textbooks on reading interest of students, (7) the influence of campus environment against reading interest of students, (8) the effect of teaching methods to the reading interests of students, (9) the influence of motivation to read to reading interest of students, (10) the factors that influence the views from the learning habits of students, availability of textbooks, campus environment and learning methods to interest in reading with variable between motivation, in Politeknik Negeri Malang (Polinema).Sampel used in this research consisted of 137 respondents are students majoring in electrical engineering semesters IV, primary data collected through questionnaires.Technique data analysis using path analysis.This study found evidence that: (1) Study Habits positive influence and significant impact on motivation. (2) Availability of textbooks have a positive influence and significant impact on motivation. (3) environmental campus positive effect significantly to the motivation. (4) learning method influential no significant effect on motivation. (5) Study Habits direct and indirect positive effect and significant interest in reading. (6) Availability of books Lessons are directly and indirectly affect positively but not significant interest in reading (7) Environment campus in direct and indirect positive effect and significant to the interest in reading (8) method of learning directly and not trim a positive effect and significant interest in reading. (9) Motivation positive effect and significant interest in reading. (10) learning habits, the availability of textbooks, campus environment, learning methods and significant positive effect on student interest in reading at Polinema.Â Keywords:learning habits, availability of textbooks, campus environment, teaching methods, motivation and interest in reading